Assessment Ketersediaan Beras Pada 34 Provinsi di Indonesia - Marzani, Yura; Juliannisa, Indri Arrafi (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Indonesia is an agricultural country, which means that the agricultural sector plays an important role in supporting the national economy. The agricultural sector has a very significant contribution to achieving the goals of the two Sustainable Development Goals (SDGs) programs, namely no hunger, achieving food security, improving nutrition and encouraging sustainable agricultural cultivation. Food crops are included in the main products of the agricultural sector in Indonesia. One of the food crops that has an important role as a supporter of food security is the rice commodity. In this study, Indonesia became the object of research using data for 2020 from 34 provinces in Indonesia. In examining the condition of rice availability from 34 provinces in Indonesia, this study used the Multi Criteria Decision Making "PROMETHEE" method with eight criteria or variables namely rice production, rice consumption, population, paddy field area, agricultural technology, GRDP per capita, inflation, and market size. Based on the results of the research that has been done, it can be concluded that of the 34 provinces that have been ranked through outranking, there are 14 provinces that have positive Phi values, and 20 provinces that have negative Phi values. The provinces with the best rice availability were South Sulawesi, Central Kalimantan and East Java, while the provinces with the lowest rice availability were Gorontalo, Papua and DKI Jakarta.